eHealth Literacy and Gender Disparities: Insights from an Internal Survey - Manes, MT; Mannarini, A; Pavan, D; Aschieri, D; Khoury, G; Scardovi, B; Bruno, N; Cocozza, S; Gabrielli, D; Colivicchi, Furio; Grimaldi, Massimo; Oliva, Fabrizio (Journal of Cardiology and Cardiovascular Medicine, 2024)
The increasing reliance on digital health services, particularly in light of recent global health crises, has highlighted the importance of eHealth literacy. This study explores the role of eHealth literacy in managing health outcomes, with a specific focus on gender disparities. Using data from the “Truck Tour-Banca del Cuore 2023” survey, which included 354 participants, we examined how integrated technology influences health monitoring and management strategies. Our findings underscore the critical role of eHealth literacy in improving health outcomes and reducing gender disparities, particularly in the context of digital health interventions.